JOUR-MAS: a multi-agent system approach to help journalism management - López Barriuso, Alberto; De La Prieta, Fernando; Lozano Murciego, Álvaro; Hernández, Daniel; Revuelta Herrero, Jorge (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2015)
Nowadays, the vertiginous progress of technology has led society to demand lower response times in general, but in press in particular. For this reason, media groups have to face a big challenge in order to facilitate their employees the technical means that enable professionals in the media sector to face the new communication models. In this article, we face this problem and present a novel system based on Virtual Organizations of agents and Cloud Computing in order to improve the organization, management and distribution of media contents.